QUALITY OF COLOSTRUM IN DAIRY BREED COWS WITH DIFFERENT DAIRY PRODUCTIVITY - S. V. Karamayev; L. N. Bakayeva; N. A. Balakirev; V. A. Demin; A. S. Karamayeva; N. V. Soboleva; L. V. Sycheva; Yu. A. Yuldashbayev; D. A. Baimukanov (Scientific Journal of Pedagogy and Economics, 2019)
When the primary immunity is formed in the body of a newborn calf, the main source of immunoglobulins, lysozyme, functionally active leukocytes, and lymphocytes is colostrum. A very important condition for the formation of complete immunity is the quality of colostrum. A number of scientists claim that cows of different dairy breeds differ significantly in terms of dairy productivity, while the mass fraction of immunoglobulins negatively correlates with the amount of colostrum during the first milking. The main task of research was to study the dynamics of the quality of colostrum, depending on the size of the milk yield of cows for lactation. The object of the research was the cows of four breeds ща the Samara region: Black-and-white, Bestuzhev, Holstein, Ayrshire. It has been established that the content of immunoglobulins in the colostrum of the first milk yield in cows of different breeds changes under the influence of the level of dairy productivity, as well as with the age of animals. The highest content of immunoglobulins was in the colostrum of the Bestuzhev breed - 103.35-81.38 g/l, and the lowest in the Holstein breed - 74.52-42.29 g/l. Colostrum immunoglobulins are divided into three classes - IgG, IgA, IgM. In the colostrum of the first milk yield of the Black-and-white cows, the IgG level is 84.1-85.5%, Bestuzhev - 85.7-86.3%, Holstein 83.9-84.4%, Ayrshire - 85.7-86, 6%. There is a tendency to increase of IgG level, with increasing milk yields of cows for lactation. It was found that with an increase in the dairy productivity of cows, the quality of colostrum decreases and the incidence of calves grows. As a result, the average daily gain in live weight of the young stock is reduced proportionally. Based on the obtained results, we recommend assessing the quality of colostrum of the first milk yield using an optical or digital refractometer as well as to conduct targeted breeding work in the direction of improving the quality of colostrum.